TRADISI NGEREBEG PADA ERA MODERN DI DESA TEGALLALANG KECAMATAN TEGALLALANG KABUPATEN GIANYAR - Ida Ayu Gede Purnayatti Mandhara; Ni Nengah Selasih; I Putu Agus Aryatnaya Giri (Upadhyaya : Jurnal Penelitian Pendidikan, 2023)
Bali with a myriad of traditions and cultures that have been passed down from generation to generation. The development of villages and areas will affect the sustainability and culture. An example is the Ngerebeg Tradition in Tegallalang Village. The uniqueness of this tradition is that participants who follow the Ngerebeg Tradition are required to color their bodies with colorful paints, this is what distinguishes this tradition from other traditions. The problems that will be discussed include (1) How is the implementation of the Ngerebeg Tradition in Tegallalang Village, Tegallalang District, Gianyar Regency in the modern era (2) What are the implications of the Ngerebeg Tradition in applying the Tri Hita Karana teachings in Tegallalang Village, Tegallalang District, Gianyar Regency in the modern era (3) What values ​​are contained in the Ngerebeg Tradition in Tegallalang Village, Tegallalang District, Gianyar Regency. The theory used to analyze the problem is the religious theory of Koentjaraningrat, the structural functional theory of Talcott Parsons, the theory of value from Tarigan. The method used for data collection in this study is the technique of observation, interviews, documentation studies, document recording techniques. The data that has been collected was analyzed using a qualitative descriptive analysis method with steps of data reduction, data presentation, inference and verification. Based on the data analysis carried out, the results obtained: The implementation of the Ngerebeg Tradition is still carried out today due to history, The existence of the Ngerebeg Tradition began with the construction of the Duur Bingin Temple by Tjokorda Made during the war with the Dalem Sukawati kingdom. Supported by 11 families, at that time there was a ceremony at Duur Bingin Temple and residents of nunas ica asked wong samar to help with his work, until now the Ngerebeg tradition is held to honor wong samar. The Ngerebeg tradition is still carried out with the aim of neutralizing the environment in Tegallalang Village. The series of Ngerebeg traditions begins with the preparation stage and continues with the peak of the Ngerebeg tradition. The implication of the Ngerebeg Tradition is to establish a harmonious relationship with God Almighty, to establish a harmonious relationship with the natural environment in Tegallalang Village, to establish a harmonious relationship with fellow Tegallalang Village community.